Narrativas en conflicto: columnas de opinión y construcción mediática del estallido social chileno (2019) - Romero Lizama, Pamela (2025)
This article examines media narratives surrounding Chile’s 2019 social outburst through the analysis of 782 opinion columns published between October and December in print outlets linked to what journalism scholars call the “ideological duopoly” of El Mercurio–Copesa, and in independent digital media. Using quantitative content analysis, the study compares narrative framings along three dimensions: the legitimacy of protests, the evaluation of protesters and institutions, and the representation of state violence. Findings reveal significant differences: duopoly outlets tended to stress frames of order, threat, and delegitimization, whereas independent media emphasized understanding social discontent and recognizing collective action as legitimate. Moreover, mainstream outlets systematically omitted references to state violence, limiting its public problematization. The study also identifies a gender gap, with only 15% of the columns authored by women, reducing narrative diversity in a context where feminist demands were central. The article concludes that opinion journalism played a crucial role in shaping meanings during the crisis, either reinforcing or challenging hegemonic discourses, and highlights the need for greater pluralism, authorial diversity, and the recognition of conflict as constitutive of the social sphere.